Faktor yang Berhubungan dengan Kecelakaan Kerja dan Penyakit Akibat Kerja pada Nelayan Pencari Teripang di Kelurahan Namosain Kota Kupang - Martonix Abraham Tafui; Anderias Umbu Roga; Indriati A. Tedju Hinga (Universitas Nusa Cendana, 2021)
This study aims to determine the risk of education, age, period of work, frequency and duration of diving to the incidence of work-related accidents and diseases in divers fishing for sea cucumbers in Namosain Village, Alak District, Kupang City. The study was quantitative using an analytical survey. The sample consisted of 37 sea cucumber divers selected by applying the total sampling technique. The results of this study showed that age, work period, frequency and duration for diving were related to accidents and diseases while education was found unrelated with the accidents and diseases. It is recommended to establish an occupational-related post for regular check-up among fishermen, and for health promotion intervention. The fishermen also need to prevent accident and diseases by obtaining accurate information about the harmful effects of diving without using complete personal protective equipment.